Simultaneous Impact of Deep Habits Consumption and Price Stickiness on the Transmission of Monetary and Fiscal Shocks using the MS-DSGE Model - Narmin Davoudi; Hassan Heidari (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2021)
The role of deep hapbit in countercyclical behavior of mark-up and its impact on the transmission of monetary and fiscal shocks have already been studied, but its strength in the presence of Philips curve with price stickiness is not clear. The purpose of this study is to develop a New Keynesian Philips Curve (NKPC) following Cristiano et al. (2005), to investigate the simultaneous effect of price stickiness and deep habits on monetary and fiscal shock transmission using Markov- switching stochastic dynamic general equilibrium (MS-DSGE) model for the Iranian economy. The results of impulse-response functions show reducing markup for one period due to deep habits and then increasing markup and inflation after a period due to a stronger role of price stickiness. Moreover, although the negative effect of wealth due to government spending is compensated by deep habits consumption and thus makes consumption increase, it is weak in comparison to the strength of expected inflation, and therefore, inflation increases eventually. Overall, the results of this study indicate that deep habits cannot be a dominant factor in the transmission of monetary and fiscal shocks, but according to the obtained impulse response functions, it can be the strong reason to delay increasing inflation. Also, deep habits consumption can be a good reason for increasing consumption and compensating of the negative effect of wealth due to fiscal shock.